Kedudukan Dan Peranan Kantor Pertanahan Sebagai Mediator Dalam Penyelesaian Sengketa Batas Tanah - Mahendra Tri Hartarto; Adonia Ivone Laturette; Jenny Kristiana Matuankotta (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Land is an object that is vulnerable to disputes and problems regarding ownership and boundaries.Purposes of the Research:  Reviewing and analyzing the position and role of the Land Office as a Mediator in Settlement of Land Boundary Disputes, and efforts to resolve land boundary disputes at the Ambon City Land Office can be carried out in accordance with the provisions and binding according to the laws and regulations.Methods of the Research: This research was carried out in a normative juridical manner by using Statute Approach and a Conceptual Approach.Results of the Research: This research resulted in the substance that the position of the Land Office as a mediator in the settlement of land boundary disputes is as a government agency carrying out governmental tasks in the land sector. The task of the government in the land sector in question is the formulation and implementation of policies in the field of handling and preventing disputes and conflicts as well as the handling of land cases as well as the formulation and implementation of policies in the field of land surveying and mapping. The role of the Land Office as a mediator in mediating the settlement of land boundary disputes is to try to become a medium for the resolution of land boundary disputes by implementing a legal system to create justice and legal certainty. registered by the parties at the District Court where the jurisdiction of the land is located, so that it can be concluded that the results of mediation at the Land Office can have binding legal force.